High Intensity Physical Rehabilitation Later Than 24 h Post Stroke Is Beneficial in Patients: A Pilot Randomized Controlled Trial (RCT) Study in Mild to Moderate Ischemic Stroke - Tong, Yanna; Cheng, Zhe; Rajah, Gary B.; Duan, Honglian; Cai, Lipeng; Zhang, Nan; Du, Huishan; Geng, Xiaokun; Ding, Yuchuan (Frontiers in Neurology, 2019)
Objective: Very early mobilization was thought to contribute to beneficial outcomes in stroke-unit care, but the optimal intervention strategy including initiation time and intensity of mobilization are unclear. In this study, we sought to confirm the rehabilitative effects of different initiation times (24 vs. 48 h) with different mobilization intensities (routine or intensive) in ischemic stroke patients within 3 groups. Materials and Methods: We conducted a randomized and controlled trial with a blinded follow-up assessment. Patients with ischemic stroke, first or recurrent, admitted to stroke unit within 24 hours after stroke onset were recruited. Eligible subjects were randomly assigned (1:1:1) to 3 groups: Early Routine Mobilization in which patients received <1.5 h/d out-of-bed mobilization within 24-48 h after stroke onset, Early Intensive Mobilization in which patients initiated ≥3h/d mobilization at 24-48 h after the stroke onset, and Very Early Intensive Mobilization in which patients received≥3h/d mobilization within 24 h. The modified Rankin Scale score of 0-2 was used as the primary favorable outcome. Results: We analyzed 248 of the 300 patients (80 in Early Routine Mobilization, 82 in Very Early Intensive Mobilization and 86 in Early Intensive Mobilization), with 52 dropping out (20 in Early Routine Mobilization, 18 in Very Early Intensive Mobilization and 14 in Early Intensive Mobilization). Among the three groups, the Early Intensive Mobilization group had the most favorable outcomes at 3-month follow-up, followed by patients in the Early Routine Mobilization group. Patients in Very Early Intensive Mobilization received the least odds of favorable outcomes. At 3 month follow up, 53.5%, (n=46 ) of patients with Early Intensive Mobilization showed a favorable outcome (modified Rankin Scale 0-2)(p=0.041) as compared to 37.8% (n=31) of patients in the Very Early Intensive Mobilization. Conclusions: Post-stroke rehabilitation with high intensity physical exercise at 48 h may be beneficial. Very Early Intensive Mobilization did not lead to a favorable outcome at 3 months. Trial registration: ChiCTR-ICR-15005992.